UnoHop: Efficient Distributed Hash Table with O(1) Lookup Performance - Herry Sitepu; Carmadi Machbub; Armein Z. R. Langi; Suhono H. Supangkat (Journal of ICT Research and Applications, 2008)
Distributed Hash Tables (DHTs) with O(1) lookup performance strive to minimize the maintenance traffic required for disseminating membership changes information (events). These events dissemination allows each node in the peertopeer network maintains accurate routing tables with complete membership information. We present UnoHop, a novel DHT protocol with O(1) lookup performance. The protocol uses an efficient mechanism to distribute events through a dissemination tree that is constructed dynamically rooted at the node that detects the events. Our protocol produces symmetric bandwidth usage at all nodes while decreasing the events propagation delay.